Screening for novel factors involved in mouse early embryonic development using inhibitor libraries - Nishizono, Hirofumi; Kato, Masaki (Frontiers in Cell and Developmental Biology, 2025)
Mammalian early embryonic development is regulated by numerous factors, yet not all have been identified. Although omics approaches such as next-generation sequencing and proteomics provide powerful tools, screening methods using inhibitor libraries remain highly effective for identifying novel factors involved in embryonic development. To this end, we developed a novel screening system that combines ultra-superovulation technology with one-cell stage embryos cryopreservation in mice. Using this system, we screened 95 inhibitors to identify factors essential for the development of mouse fertilized eggs and identified 16 factors, including 5 previously known ones. Among the known factors, two were ATPases, and our data confirmed that inhibition of different ATPase types arrested embryonic development at distinct stages. In addition, we discovered novel regulators affecting various developmental stages, including a p53 activator (PRIMA-1), cathepsin D, CXCR2, and potassium channels (SK2 and SK3). Genome editing experiments involving knockout of the cathepsin D and CXCR2 genes further verified the arrest of embryonic development. These results demonstrate that our developed screening method can effectively identify novel factors involved in embryonic development. Application of this approach to additional inhibitor libraries and other species may facilitate the discovery of further species-specific regulators of early embryonic development.